Latinos in Nevada : A Political, Economic, and Social Profile - Tuman, John P. (John Peter), 1964-; Kopalyan, Nerses; Damore, David, 1970-; Howard, Tiffiany (Book collections on Project MUSE., 2021)
"Latinos in Nevada: A Political, Economic, and Social Profile provides a political, economic, and demographic profile of contemporary Latinos in Nevada. Adopting an interdisciplinary perspective, the authors examine Latino history, growth, and trends in employment, education, and health, and analyze the dynamics of political participation and civic engagement"--